Antimicrobial activity of extracs from Ageratina neriifolia (Asteraceae) - Velasco, Judith; Barreto, Silvio; Buitrago, Diolimar; Vivas, Rosana (Ciencia, 1970)
The an ti mi cro bian ac ti vity of etha nol, ace to ne and aqueous ex tracts of the ae real parts of Age ra ti na ne rii fo lia (As te ra ceae) were eva lua ted againts Staphylococcus aureus (ATCC 25923), Enterococcus faecalis (ATCC 29212), Escheri chia coli (ATCC 25992), Pseudomonas aeruginosa (ATCC 27853) and Can di da al bi cans (ATCC 90028), using the disc diffu sion method. Only the ace to nic and etha no lic ex tracts showed ac ti vity against S. au reus, E. fae ca lis, pro ving that the com pounds pre sent in A. ne rii fo lia are ac ti ve againts Gram po si ti ve bac te rias. This is the first time an ti mi cro bian ac ti vity has been re por ted for this spe cies.